1991
DOI: 10.2165/00003495-199142020-00009
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Granulocyte Colony-Stimulating Factor (rG-CSF)

Abstract: Recombinant granulocyte colony-stimulating factor (rG-CSF) is a glycoprotein hormone which has been produced in mammalian cells and, in a nonglycosylated form, in the bacterium Escherichia coli through recombinant DNA technology. It stimulates proliferation, differentiation and activation of cells of the neutrophil-granulocyte lineage and has been investigated as therapy for patients with various neutropenic conditions, both iatrogenic and disease related. rG-CSF is well tolerated, the most frequently reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(16 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…In both neutropenic and non-neutropenic subjects, G-CSF administration has been extensively shown to rapidly elevate circulating polymorphonuclear leucocyte (PMN) counts in a dose-dependent fashion (Hollingshead & Goa, 1991). The present study also shows that the administration of 2 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In both neutropenic and non-neutropenic subjects, G-CSF administration has been extensively shown to rapidly elevate circulating polymorphonuclear leucocyte (PMN) counts in a dose-dependent fashion (Hollingshead & Goa, 1991). The present study also shows that the administration of 2 .…”
Section: Discussionsupporting
confidence: 63%
“…In both neutropenic and nonneutropenic subjects, G-CSF has been found to rapidly increase the number of circulating PMN in a dose-dependent fashion and has therefore been investigated as therapy for patients with various neutropenic conditions (Bensinger et al, 1993;Hollingshead & Goa, 1991). G-CSF has also been shown to potently stimulate or enhance certain effector functions of mature human PMN, these being properties that are primarily related to hose defence against invading pathogens (Demitri & Griffin, 1991).…”
mentioning
confidence: 99%
“…Moreover, all three became afebrile within 24 h after initiation of G-CSF treatment, although the ANCs were not substantially in creased in two of them at that time. This might support a stimulatory effect on the mature circulating neutrophils, as has been pointed out by other authors [6,7]. No patient suffered any adverse reaction.…”
supporting
confidence: 86%
“…It has a selective effect on the granulocytic precursors resulting in an apparent rise of circulating neutrophils [5][6][7]. Al though, there is not much experience with G-CSF as a treatment for toxic neutropenias [8][9][10], the reported re sults, all of them anecdotal, are promising.…”
mentioning
confidence: 99%
“…This hematopoietic factor does not show species boundary and therefore rh G-CSF has been used in experimental animals [11], A recent report has suggested that rh G-CSF possesses beneficial effects on survival and hemodynamics of ani mals subjected to septic shock. Flowever, the beneficial effects of rh G-CSF in this experimental model are ascribed to its multiple biological effects on cells of neu trophilic lineage.…”
Section: Discussionmentioning
confidence: 99%